Aging in rural communities: Engagement in indoor leisure activities and older adult health - Pei-Yi Weng; Dongying Li; Man-Li Liao; Yen-Cheng Chiang (PLoS ONE, 2025)
Aging is a pressing concern worldwide, particularly in rural communities characterized by a high aging index and an exodus of young individuals. Physical and mental well-being play key roles in older adults’ overall health. COVID-19 has resulted in limitations on the outdoor activities of older adults, negatively affecting their social interactions and health. In this study, we designed an intervention to investigate the effects of indoor leisure activities on successful aging. Three types of activities were selected: horticultural, handicraft, and baking activities, each lasting 4 weeks. 82 older adults were randomly assigned to perform the activities and completed self-reported measures regarding their activities of daily living, depression, and mental and social health. Our results indicated horticultural activities to reduce depression and significantly improve physical, mental, and social health; handicraft activities likewise significantly improved physical, mental, and social health. Thus, indoor leisure activities can enhance the physical and mental health of older adults.